APLIKASI PUPUK AB MIX TOMAT UNTUK MENINGKATKAN KEKERASAN UMBI KENTANG MELALUI TEKNOLOGI AEROPONIK - Eny Hari Widowati (JURNAL LITBANG PROVINSI JAWA TENGAH, 2015)
The Deman of potatos increase every years along with potatos consumpsion. The impactof this phenomenon is the demand of potatos seed increase.The increase of potatos seeds not offseted by the avilability of high-quality seeds. Is so its caused the using of low-quality seeds. The certification of low quality seeds 15% lower than 15%. The Aeroponic System is one of the method to result in high-quality seeds. The “AB mix tomato” fertilizer is a fertizer that contains macro and micro elements so that the tomatoes will grow big and have a hard peel .The purpose is to analyze the effect of the concentration “AB mix tomato” fertilizer aplication to the growth, production, and the quality of potato tubers. Method: The location is at Village Surengede, Districts Kejajar Wonosobo Regency, started from October until December 2015. The method is complete random plan with one factorial and was repeated twice, the concentration is P1:1,5 liter/300 liter; P2:1,8 liter/300 liter; P1:2 liter/300 liter. The analyss statistic for monitoring, growed, hight plant, the amount of oots and hard tubers. Result:1)concentration of Fertilizer usage will be effect to growed; 2)Height of the plant. During 4 weeks all of plant was not significantly all treatment, but at the age of 9 weeks at P1 significantly different than in the P2 and P3;3)Amount tubers: Treatment P1 significantly different with treatment P2 and P3;4)Hard Tubers: Hard potato tubers at harvest harvest has a hardness that is not significantly different in all treatment. Conclusion: Treatment P3 is has to effect on the growt and amount tuber, but is not to tubers hard potato.Suggestion: Optimization of growt and amount tubers is necessary to add a liquid NPK fertilizer through leaf.